Islam and Gender: An Exploration of Hadith on the Equality of Men and Women - Dadah; Muhammad Rama Ramadan; Siti Maesaroh (Journal of Religion and Social Transformation, 2024)
This study aims to explore and analyze the concept of gender equality in hadith, with the goal of providing a clearer and more comprehensive understanding of how hadith regulates the relationship between men and women in various life contexts, whether in family, social, or professional domains. This study employs a qualitative method with a content analysis approach. The primary data sources are collections of hadith relevant to the topic of gender equality, gathered from various trusted hadith compilations. The analytical techniques used include interpretation of hadith texts, comparison with related Quranic verses, and review of classical and contemporary scholars' views on this issue. The results of the study indicate that hadith generally supports the principle of gender equality in many aspects, although there are some hadiths that require historical and sociocultural context to be comprehensively understood. These hadiths, if interpreted correctly and contextually, show that Islam provides equal rights and responsibilities between men and women and encourages respect and gender justice. However, the interpretation and implementation of gender equality in Muslim societies are often influenced by local cultural and traditional factors, which sometimes deviate from the true essence of Islamic teachings. This study highlights the importance of a critical and contextual approach in understanding hadith texts to support efforts in achieving gender equality that is just and in accordance with Islamic values.